The reflection of generation Z of leisure practices in Chinese audiovisual media: An analysis based on the YouTube platform - Gavra, Dmitrii P.; Fu, Lisha (Edelweiss Applied Science and Technology, 2024)
This study explores the reflection of Generation Z leisure culture in Chinese audiovisual media, with a focus on the YouTube platform. As China’s Generation Z becomes a key demographic in shaping digital and media consumption patterns, their leisure practices reflect a unique fusion of local and global influences. Through an analysis of content on YouTube, this research examines how audiovisual media portrays the leisure activities of Chinese Generation Z, including entertainment, social interaction, and self-expression. By investigating the cultural narratives and visual strategies used to engage this generation, the study reveals how YouTube serves as a platform for identity formation, a strong sense of national identity, and pride in Chinese traditional culture among Chinese Gen Z audiences. The findings contribute to understanding the broader impact of digital platforms on leisure habits and media discourse in contemporary China, highlighting the transformative role of audiovisual media in shaping youth culture. It also plays a significant cultural education function, enhancing the positive perception of Chinese culture on the international stage and elevating China’s image.